PENGARUH METODE PENCUCIAN SPERMATOZOA SAPI ACEH TERHADAP MOTILITAS, PERSENTASE HIDUP, DAN INTEGRITAS MEMBRAN PLASMA UTUH SPERMATOZOA (The Infuence of Aceh Bull Spermatozoa Washing Method on Spermatozoa Motility and Plasma Membrane Integrity of Intact Spermatozoa) - Listin Handayani; Dasrul Dasrul; Muslim Akmal; Cut Nila Thasmi; Hamdan Hamdan; Mulyadi Adam (Universitas Syiah Kuala, 2015)
This study aimed to determine the effect of sperm washing by swim up and centrifugation in isotonic medium on sperm quality of aceh bull. In this study, fresh semen from healthy male aceh bull aged 3-4 months was collected using artificial vagina. Immediately after semen collection, fresh semen quality was examined macroscopically and microscopically. Subsequently, sperm washing was performed by centrifugation and swim up in sperm washing medium. Group 1 (P0) as control group, cement washed with isotonic solution (andromed medium: saline solution) with ratio of 1:8. 2. Group 2 (P1), cement was separated by centrifugation method, group 3 (P2), all cement was separated by swim up method then examined the sperm quality sperm washing results. Each treatment was repeated 5 times. Quality parameters measured were the percentage of spermatozoa motility, sperm viability, and plasma membrane integrity intact spermatozoa. Data were analyzed with analysis of variance one-way pattern, followed by Duncan's multiple test. The results showed the mean ± SD percentage of sperm motility of each treatment group (P0; P1; P2) respectively amounted to 72.00±3.74, 66.40±4.77, and 73.60±3.29%. The percentage of viability was 72.00 ±3.74%, 66.40±2.88%, 71.80±2.17%. The percentage of plasma membrane integrity is intact spermatozoa was 68.20±1.79%, 57.20±3.77%, 69.00±2.00%. Results of this study showed that the percentage of motility, live spermatozoa and plasma membrane integrity intact after separation by swim-up method were significantly different (P 0.05) compared with no separation.Key words: spermatozoa quality, aceh bulls, centrifugation, swim up